2001
DOI: 10.2166/wst.2001.0729
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the efficacy of ozonation for inactivating Cryptosporidium parvum oocysts

Abstract: Examination of the effects of water temperature on the inactivation of Cryptosporidium parvum oocysts with ozone, ozonation experiments were conducted in a semi-batch mode with a wide temperature range of 3-30 degrees C. Inactivation was assessed in terms of mice infectivity and in vitro excystation. The temperature dependency of the CT products by a reduction in infectivity of 2 log10 could be described successfully by the Arrhenius equation, 1/CT = 1.086 x 10(18)e-12520/K where CT is the integrated ozone con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The estimated UV dose for a 2-log 10 reduction in viability at 20°C was 230 mWs/cm 2 , which is approximately 200 times higher than the dose required for an equivalent reduction in infectivity. Hirata et al reported that the CT (product of concentration of disinfectant and contact time) values of chemical disinfectants required for equivalent reductions in the infectivity and the viability of C. parvum differed by a factor of 18 for chlorine (12) and by a factor of 3 for ozone (13). The present study showed a marked difference between the effect of UV irradiation on the infectivity of C. …”
Section: Resultsmentioning
confidence: 40%
See 1 more Smart Citation
“…The estimated UV dose for a 2-log 10 reduction in viability at 20°C was 230 mWs/cm 2 , which is approximately 200 times higher than the dose required for an equivalent reduction in infectivity. Hirata et al reported that the CT (product of concentration of disinfectant and contact time) values of chemical disinfectants required for equivalent reductions in the infectivity and the viability of C. parvum differed by a factor of 18 for chlorine (12) and by a factor of 3 for ozone (13). The present study showed a marked difference between the effect of UV irradiation on the infectivity of C. …”
Section: Resultsmentioning
confidence: 40%
“…The CT requirement of chemical disinfectants generally depends on both the temperature and the concentration of the disinfectant (5, 13). For instance, the temperature factor of ozone has been reported to be as high as 4.09 (16) or 4.20 (13) for every 10°C reduction in temperature. However, temperature did not significantly affect the efficacy of UV irradiation in reducing the infectivity of oocysts in this study.…”
Section: Vol 68 2002 Uv Irradiation For Inactivation Of C Parvum Omentioning
confidence: 99%
“…In order to determine whether C. parvum oocysts are digested by H. schlegeli clams, or whether they remain infectious after ingestion in vitro, qualitative detection of C. parvum oocysts obtained from clam feces was carried out using cultured human colon tumor (HCT-8) cells, as reported elsewhere (19,45,48) and described briefly below.…”
Section: Preliminary Investigations Of H Schlegeli (I) Facilities Fmentioning
confidence: 99%
“…The supernatant was aspirated and the pellet was resuspended in 100 ml PBS (pH 7.4). A pre-incubation procedure was performed by mixing the sample with acidified Hank's balanced salt solution (HBSS) and incubated at 378C for 30 min (Hirata et al 2001). The washed pellet was resuspended in 100 ml of PBS and 10 ml of 1% (w/v) sodium deoxycholate in Hank's minimal essential medium and mixed with 10 ml of 2.2% (w/v) NaHCO 3 in HBSS.…”
Section: Excystationmentioning
confidence: 99%
“…The washed pellet was resuspended in 100 ml of PBS and 10 ml of 1% (w/v) sodium deoxycholate in Hank's minimal essential medium and mixed with 10 ml of 2.2% (w/v) NaHCO 3 in HBSS. The samples were incubated at 378C for 4 h as described previously (Robertson et al 1993;Vesey et al 1997;Hirata et al 2001). When the excystation protocol was completed, 25 ml of sample was air-dried onto Spot-on-slides Mean excystation of ozonated water sample Mean excystation of filtered water sample from WTP £ 100…”
Section: Excystationmentioning
confidence: 99%